2020
DOI: 10.1177/0020764020910456
|View full text |Cite
|
Sign up to set email alerts
|

Role of traditional healers in the pathway to care of patients with schizophrenia in Egypt

Abstract: Background: Traditional healers are considered one of the important stages in the pathway to care of schizophrenia patients because of the confidence in the system, affordability and accessibility of the service, exposing patients to hazardous management, delay in seeking psychiatric help and bad prognosis. Aim: To assess the pathway to care of schizophrenia patients and role of traditional healers into it, the sociodemographic and clinical correlates of those patients. Methods: We assessed 232 patients with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 16 publications
2
26
2
Order By: Relevance
“…It has been reported that the popularity of traditional healers in Egypt is in part a result of the comprehensive and holistic approach they offer by encompassing the patient’s spiritual beliefs, cosmology, and world view [ 40 ]. Though psychiatric services bring tremendous value to the improvement and treatment of mental illnesses, they sometimes fail to provide care within the patient’s broader cultural framework [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the popularity of traditional healers in Egypt is in part a result of the comprehensive and holistic approach they offer by encompassing the patient’s spiritual beliefs, cosmology, and world view [ 40 ]. Though psychiatric services bring tremendous value to the improvement and treatment of mental illnesses, they sometimes fail to provide care within the patient’s broader cultural framework [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…The General Health Questionnaire administered to over 25,000 individuals in Egypt estimated a prevalence of 24.9% for psychiatric comorbidity, and these mainly included mood (depressive), anxiety, and substance use disorders [ 4 ]. Importantly, people with mental illness in Egypt and other Arab countries tend to somaticize their psychological symptoms and often seek traditional healers for most types of mental and physical health problems owing to societal acceptance, affordability, and accessibility [ 5 , 6 ]. Stigmatizing attitudes toward people with mental illness contributes to a reluctance to seek psychiatric care, and similarly, expensive and inaccessible psychiatric care deters individuals from the mental health system, which is characterized by a relevant shortage of human resources [ 5 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…2009), more socially accepting of distressing experiences and often more accessible for service users and their family (Ibrahim Awaad et al . 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, developing an understanding of the perception of this therapeutic relationship and how this can be enhanced in online trials is important for facilitating use and enhancing persistence with interventions once the individual is engaged. This might be particular to the context of Egypt; two recent studies in Egypt show that service users in Egypt report lack of trust of the mental health system generally, which might explain the lack of trust in the efficacy in a predesigned online intervention (Ibrahim Awaad et al, 2020; Kamel et al, 2020). These studies also show that this barrier is overcome in Egyptian samples with communication and building therapeutic relationship.…”
Section: Discussionmentioning
confidence: 99%